2010
DOI: 10.1016/j.schres.2009.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clozapine and olanzapine on cortical thickness in childhood-onset schizophrenia

Abstract: Background: Little is known about the effects of antipsychotic medications on gray matter (GM) in schizophrenia. Although clozapine remains the most effective antipsychotic medication in treatment-refractory cases, it is unknown whether it has a differential effect on GM development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
(44 reference statements)
2
26
0
3
Order By: Relevance
“…Our finding of cortical thinning is also consistent with a small study of patients with childhood-onset schizophrenia who demonstrated a similar cortical thinning trajectory when treated with either olanzapine or clozapine, with the authors noting that patients treated with clozapine displayed a region of significant thinning compared with patients treated with olanzapine in the RPFC (Mattai et al, 2010). These studies tentatively suggest that patients treated with clozapine may suffer greater cortical gray matter loss than other patients with schizophrenia; however, as these studies like ours are observational in design, it is not possible to identify whether clozapine treatment is the pathophysiological factor involved in the gray matter loss, or whether other factors such as more malignant illness with associated accentuated tissue loss are causative.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of cortical thinning is also consistent with a small study of patients with childhood-onset schizophrenia who demonstrated a similar cortical thinning trajectory when treated with either olanzapine or clozapine, with the authors noting that patients treated with clozapine displayed a region of significant thinning compared with patients treated with olanzapine in the RPFC (Mattai et al, 2010). These studies tentatively suggest that patients treated with clozapine may suffer greater cortical gray matter loss than other patients with schizophrenia; however, as these studies like ours are observational in design, it is not possible to identify whether clozapine treatment is the pathophysiological factor involved in the gray matter loss, or whether other factors such as more malignant illness with associated accentuated tissue loss are causative.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, widespread cortical thinning was demonstrated longitudinally in the patient group compared with controls, a finding consistent with previous literature (Nesvåg et al, 2008;Sprooten et al, 2013). Cortical thinning has been reported to be largely unrelated to the type of antipsychotic medication prescribed including Brain atrophy post clozapine treatment M Ahmed et al clozapine (Nesvåg et al, 2008;Mattai et al, 2010;Hirjak et al, 2014); however, atypical antipsychotic agents and in particular clozapine have also been associated with an attenuation of cortical thinning in the frontal lobe (van Haren et al, 2011). In this study, treatment (NRs had greater cortical thinning in the right middle temporal and left medial frontal cortex.…”
Section: Discussionsupporting
confidence: 90%
“…Although this is not the place to develop such a theme further, the power of certain drugs, such as clozapine and indeed lithium, to promote the growth of new synapses has been extensively examined in animal models (Critchlow et al 2006;Kim and Thayer 2009). More recently it has been shown that olanzapine can arrest the loss of grey matter in certain parts of the brain of young adolescents suffering from schizophrenia (Mattai et al 2010). Clearly this is an exciting area of research and opens up the possibility that courts in the future might be able to direct that the accused receive such support.…”
Section: Conclusion: a Mcnaughton Rule And Cognitive Neurosciencementioning
confidence: 99%
“…18 Van Haren et al 19 investigated white and gray matter density in a longitudinal study and reported that the dose of clozapine accumulated per year during the 5-year follow-up study was related to a smaller reduction in density in the region of the left superior frontal gyrus compared with typical antipsychotic therapy. In a study comparing patients on clozapine and olanzapine, another atypical antipsychotic, Mattai et al 20 assessed gray matter cortical thickness and found the use of clozapine to be associated with thickness reduction in an area of the right prefrontal cortex.…”
Section: Structural Studiesmentioning
confidence: 99%